2016
DOI: 10.1002/2015gl067543
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of long‐term aerosol optical depth series with sunshine duration records

Abstract: We report the suitability of sunshine duration (SD) records as a proxy for the reconstruction of atmospheric aerosol content, for which little information exists, especially prior to the 1980s. Specifically, we have treated cloudless summer days in 16 stations throughout Spain. For almost all sites we find statistically significant relationships between aerosol optical depth (AOD) and daily SD. The correlation coefficient presents a mean value of −0.72, and slope values of the linear regressions are within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
2
15
0
3
Order By: Relevance
“…This suggested that during the global dimming/brightening periods there is an important fraction of SD evolution that cannot be explained by cloud cover changes which must therefore depend on other factors such as changes in aerosol optical thickness. The temporal variations in aerosol optical thickness of the last decades seem to be mainly driven by anthropogenic emissions (Streets et al, 2006(Streets et al, , 2009, even though, especially for southern Italy, mineral particles originating from Sahara and Sahel areas may also have a significant role, as recently suggested for Spain by Sanchez-Romero et al (2016). This natural atmospheric aerosol, with emissions that are highly variable from year to year, is a significant component of the Mediterranean area Varga et al, 2014) causing reflection and absorption of the incoming solar radiation and therefore affecting the energy balance together with anthropogenic aerosols (Zhu et al, 2007).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This suggested that during the global dimming/brightening periods there is an important fraction of SD evolution that cannot be explained by cloud cover changes which must therefore depend on other factors such as changes in aerosol optical thickness. The temporal variations in aerosol optical thickness of the last decades seem to be mainly driven by anthropogenic emissions (Streets et al, 2006(Streets et al, , 2009, even though, especially for southern Italy, mineral particles originating from Sahara and Sahel areas may also have a significant role, as recently suggested for Spain by Sanchez-Romero et al (2016). This natural atmospheric aerosol, with emissions that are highly variable from year to year, is a significant component of the Mediterranean area Varga et al, 2014) causing reflection and absorption of the incoming solar radiation and therefore affecting the energy balance together with anthropogenic aerosols (Zhu et al, 2007).…”
Section: Introductionmentioning
confidence: 81%
“…Specifically, we represent the length of the period considered for the analysis (y axes) in relation to the starting year of the window that the trend refers to (x axes). Slopes are shown by means of the colors of the corresponding pixels, with large squares for trends with a significance level of p ≤ 0.1 and small squares for trends with a significance level of p > 0.1 (considered here statistically non-significant), with significance levels estimated by means of the Mann-Kendall nonparametric test (Sneyers, 1992).…”
Section: Trend Analysis Of the All-sky Ssr Recordsmentioning
confidence: 99%
“…The device (sunshine recorder) for measuring sunshine hours is simple (more details in Section 2), but useful information can be generated from the data and can be employed in many areas of research. This data has been used in several studies, including for air quality (Sanchez-Romero et al, 2016;Li et al, 2016); environmental pollution (Kaiser and Qian, 2002;Statheropoulos et al, 1998); energy (Yaiche et al, 2014); and solar radiation prediction modelling studies (Mulaudzi et al, 2015;Adeyemi et al, 2015;Singh et al, 2011). The sunshine hour of any day is affected by varying atmospheric and sky conditions, so SD can, therefore, indirectly indicate atmospheric turbidity, visibility and sky conditions.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor parte de los resultados que se presentarán en el siguiente apartado provienen de trabajos ya publicados (Sanchez-Lorenzo et al, 2007;2009;2012;Enriquez-Alonso et al, 2015;Sanchez-Romero et al, 2016). En todas estas referencias se detalla el origen de los datos utilizados.…”
Section: Datos Y Métodosunclassified
“…Ahora bien, las observaciones directas de carga de aerosoles son escasas antes de la época de los satélites o de la generalización de instrumentos como los heliofotómetros, es decir, antes de los años 1990. Por ello el trabajo de Sanchez-Romero et al (2016) abordó la estimación de la carga de aerosoles (específicamente, de su espesor óptico, AOD) a partir de datos de insolación (para días sin nubes), que se correlacionaron con medidas directas mediante instrumentos Cimel de la red AERONET. Extrapolando hacia el pasado las relaciones entre AOD e insolación obtenidas, se obtuvo una estimación de la evolución del AOD medio para España, desde el año 1960 (ver Figura 7).…”
Section: Conclusiones Y Discusiónunclassified